Leave Earlier or Travel Faster? Optimal Mechanisms for Managing Arrival Time in Migratory Songbirds - Morbey, Yolanda E.; Hedenström, Anders (Frontiers in Ecology and Evolution, 2020)
We develop an optimization model with two decision variables to explore optimal migration mechanisms to facilitate optimal breeding timing in migratory songbirds. In the model, fitness is a function of date-dependent mortality, speed-dependent predation risk, and phenological match at arrival. The model determines the optimal combination of departure date for spring migration and migration speed, which can be mediated either by the power requirement for flight (P) or foraging effort at stopover sites (k). Our model predicts that earlier departure for spring migration should be the primary mechanism underlying earlier breeding timing, with a lesser role for faster migration via lower P or higher k. In contrast, longer migrations to breeding areas selects for both earlier departure and faster migration. Empirical data on sex-specific migration traits largely conform to model predictions, since males generally migrate earlier than females but not faster than females. In contrast, empirical data on age-specific migration traits show some disagreement with model predictions, thus implicating additional tradeoffs. In partial agreement with the model, a comparative analysis of 25 songbird species showed that populations with longer migrations migrate more quickly, but do not initiate migration earlier. Our simple model proves to be a useful framework for interpreting migration strategies in animals making costly seasonal migrations.